The effects of foam rolling vs massage as recovery tools among UiTM Perlis FC footballers / Nurul Afiqah Bakar ... [et al.] - Roslan, Muhammad Nuh Sharid; Zuraimy, Muhammad Hazim; Abdul Halim, Mohd Hazwan Zikri; Bakar, Nurul Afiqah; Ahmad, Mohd Faridz (Universiti Teknologi MARA, Perlis, 2024)
A new idea of recovery has been discovered called self-myofascial release. Foam rolling is one of the self-myofascial approaches that can help to speed up the recovery process. It works by relaxing contracted muscles, improving blood and lymphatic circulation, and stimulating the stretch reflex in muscles. However, there is no previous research that studies the comparison of recovery modalities between foam rolling (FR), massage (M) and passive recovery (PAS) as tools of the recovery process on youth footballers. The aim of this study was to examine the effectiveness of FR (20 minutes of FR exercises on quadriceps, hamstrings, adductors, gluteus, and gastrocnemius), M (20 minutes of M on quadriceps, hamstrings, adductors, gluteus and gastrocnemius) and passive recovery (20 minutes sit on a bench) interventions performed immediately after a training session on Total Quality Recovery (TQR), perceived muscle soreness (VAS), jump performance, agility, sprint, and flexibility 24 hours after the training. During the two experimental sessions, 30 UiTM FC football players participated in a randomized controlled trial design. The first session was designed to collect the pretest values of each variable. After baseline measurements, the players performed a standardized football training. At the end of the training unit, all the players were randomly assigned to the FR, M and PAS recovery groups. A second experimental session was conducted to obtain the posttest values. As results, CMJ, agility (Arrowhead) and TQR showed positive effects in the FR group in comparison with the M and PAS groups at 24 hours after training. Thus, it is recommended that football coaches and physical trainers working with football players use a structured recovery session lasting approximately 20 minutes based on FR exercises that could be implemented at the end of a training session to enhance recovery between training loads